2022
DOI: 10.29036/jots.v13i24.368
|View full text |Cite
|
Sign up to set email alerts
|

Coopetition of European Union Countries within Destination Management

Abstract: Coopetition has been the issue of various studies in different fields, but there is a research gap in examining coopetition within the tourism sector and destination management. This paper aims to determine whether there are internally homogeneous and externally heterogeneous groups of European Union countries regarding indicators of natural and cultural resources of the Travel and Tourism Competitiveness Index (TTCI), and thus subsequently identify the importance and possibilities of competition among countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Tourism is often seen as an important engine of economic growth and development in countries, helping to develop the economic well-being of local people (Tóth, Dávid & Bujdosó 2010; Mura & Kajzar, 2019;Vasanicova et al, 2022). According to Ranasinghe (2019) the tourism industry is one of the fastest-growing industries in the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourism is often seen as an important engine of economic growth and development in countries, helping to develop the economic well-being of local people (Tóth, Dávid & Bujdosó 2010; Mura & Kajzar, 2019;Vasanicova et al, 2022). According to Ranasinghe (2019) the tourism industry is one of the fastest-growing industries in the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, there is no unified understanding of the role of the shadow economy in the functioning of the economy and ensuring its stability. According to the results of the paper's analysis, it can be concluded that the shadow economy negatively affects certain sectors of economic development and the attractiveness of Lithuania (Ginevicius et al, 2021), Ukraine (Kuznyetsova et al, 2017;Shpak et al, 2022), Algeria (Ramli et al, 2022), EU countries (Roszko-Wójtowicz & Grzelak, 2020;Serpeninova et al, 2020;Vasanicova et al, 2022), Croatia (Škare et al, 2020), BRICS (Cheteni, P. & Umejesi, 2022;Tsaurai, 2022); Central Asia and Eastern Europe (Kaya & Engkuchik, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The trajectory of a good part of the economies that today make up the European Union reveals the importance of the tourism sector for their growth and development strategies, especially in those regions that have aspects to attract and maintain high flows of tourists over time (Capó & Valle, 2008;Vasanicova et al, 2022). Despite the high sensitivity of activities related to tourism to the ups and downs of the economy (as reflected by its increase in expansionary stages or its decrease when they are in periods of stagnation or economic recession), the truth is that this sector demonstrates a central role in those EU territories affected by the characteristics of rurality.…”
Section: Introductionmentioning
confidence: 99%